HEALTHY, INTEGRATED AND INNOVATIVE ADOLESCENT REPRODUCTIVE SERVICES - NUR AZIZAH; Raffiky Pinandia Sustami; Puji Lestari; shefia rahmanda (ABDIMASNU: Jurnal Pengabdian kepada Masyarakat, 2026)
Background: Adolescence is a critical period for improving mental health because more than half of mental health problems begin in adolescence and some persist into adulthood. Method: This community service activity is carried out in several stages, including: preparation, implementation which includes: Health check-up services for adolescents, Education and discussion on adolescent reproductive health in an effort to increase adolescent understanding in maintaining their reproductive health, Socialization and discussion on adolescent mental health, namely early recognition of adolescent anxiety and management of mental health disorders in adolescents. as well as evaluation and assessment of activity results.Result: After carrying out this community service activity, it was shown that the health status of adolescents was normal and the level of understanding of adolescents regarding reproductive health was mostly good, namely 72%, and almost half of adolescents had good mental health. Conclusion : Based on the results of the community service activities held at Al Amanah Plus Middle School in Dander District, Bojonegoro Regency, it can be concluded that the integrated and innovative healthy youth services implemented have successfully improved adolescents' understanding of reproductive health comprehensively. This effort is crucial in implementing Holistic Midwifery Care to improve adolescent understanding and ultimately prevent child marriage